2016
DOI: 10.4306/pi.2016.13.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cell Cycle Proteins of Peripheral Lymphocytes in Patients with Alzheimer's Disease

Abstract: ObjectiveBiological markers for Alzheimer's disease (AD) will help clinicians make objective diagnoses early during the course of dementia. Previous studies have suggested that cell cycle dysregulation begins earlier than the onset of clinical manifestations in AD.MethodsWe examined the lymphocyte expression of cell cycle proteins in AD patients, dementia controls (DC), and normal controls (NC). One-hundred seventeen subjects (36 AD, 31 DC, and 50 NC) were recruited. The cell cycle proteins CDK2, CDK4, CDK6, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…It is remarkable to note that evidence of association was based on either genetic studies for TP53, VCP, APP, HTT, and PIN1 54 57 or proven molecular mechanisms for COPS5, VCP, APP, GNB2L1, HDAC1, HTT, EP300, and TRIM32 54 , 55 , 57 63 or verified protein expression changes for COPS5, HSPA8, FSCN1, PIN1, CDK2, ELAVL1, and TCP1. 56 , 62 , 64 68 In addition, some IIHs such as FN1, VCAM1, and CDK2 were reported for a role as biomarkers for disease onset and progression, 66 , 69 , 70 while ESR1, HDAC1, and EP300 were reported for a role as potential therapeutic targets. 60 , 61 , 71 Provided all this, we expect that the remainder of the IIHs (HSP90AB1, STUB1, EGFR, HSP90AA1, PDCD6EP, HSPA4, YWHAZ, MCM7, PML, RPS3, and TUBA1A, for which no link to dementia is established yet) might hold relevance to FTD or dementias and thus should be prioritized in both genetic reassessments as well as cell biology work to explore and validate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…It is remarkable to note that evidence of association was based on either genetic studies for TP53, VCP, APP, HTT, and PIN1 54 57 or proven molecular mechanisms for COPS5, VCP, APP, GNB2L1, HDAC1, HTT, EP300, and TRIM32 54 , 55 , 57 63 or verified protein expression changes for COPS5, HSPA8, FSCN1, PIN1, CDK2, ELAVL1, and TCP1. 56 , 62 , 64 68 In addition, some IIHs such as FN1, VCAM1, and CDK2 were reported for a role as biomarkers for disease onset and progression, 66 , 69 , 70 while ESR1, HDAC1, and EP300 were reported for a role as potential therapeutic targets. 60 , 61 , 71 Provided all this, we expect that the remainder of the IIHs (HSP90AB1, STUB1, EGFR, HSP90AA1, PDCD6EP, HSPA4, YWHAZ, MCM7, PML, RPS3, and TUBA1A, for which no link to dementia is established yet) might hold relevance to FTD or dementias and thus should be prioritized in both genetic reassessments as well as cell biology work to explore and validate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…CCA in the brain has been well demonstrated experimentally in models of TBI [1115], spinal cord injury [21, 2429], stroke [30, 31], and Alzheimer’s disease (AD) [3235]; it has also been reported in clinical AD [36, 37]. Both neurons and glial cells show increased expression after CNS injury, and such changes may persist for weeks to months [810].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid β was shown to promote mTORC1 signalling and CDK2 mediated tau phosphorylation leading to increased neuronal degeneration [ 149 ]. Further, in a study conducted on lymphocytes from AD patients Kim et al (2016) reported significant to moderate upregulation of CDK2, CDK4, CDK6, cyclin B, and cyclin D cell cycle proteins compared to the samples from normal subjects [ 113 ]. An aberrant colocalization of CDK4 and p16 proteins in AD brains compared to age matched controls has been observed [ 150 ].…”
Section: Dysregulated Cell Cycle In Various Neurodegenerative Disordementioning
confidence: 99%